GAMBARAN RESILIENSI PADA MANTAN PENGGUNA METHAMPHETAMINE HYDROHLORIDE PASCA MENJALANI REHABILITASI - Elisa Arli Tunggal; Nurlaila Effendy (Universitas Katolik Widya Mandala Surabaya, 2018)
Methamphetamine hydrochloride is known as methamphetamine or sabu which is a synthetic addictive substance that can be easily found in society. Individuals suffer from methamphetamine addiction require to go through rehabilitation to recover and stop the risk of substance tolerance. After rehabilitation, individuals need to have an ability to maintain the recovery process and avoid relapse. This study aimed to explore resilience ability former and in-depth interview technique. Data were gathered from three informants who were former methamphetamine users and had gone through rehabilitation. The result showed an internal condition called resilience and an external condition supporting the resilience ability of informants in order not to relapse. The internal conditions found in this study were attitude towards challenges, self-endurance and positive self-concept. Attitude towards challenges includes avoiding methamphetamine usage, resisting the urge to use methamphetamines, avoiding relationships with other drugs users, realizing their sense of worth, and being aware of their responsibilities and social life. Self-endurance is shown in the form of altering mindset to be more rational, believing in the Almighty God and conducting positive activities. Positive self-concept includes recognizing their strengths, positive emotions, positive mindset, and positive behaviour. In addition to internal conditions, this study also found external condition that supports resilience, which is positive relationship with people that they love and care.